The vaccine against Human Papilloma Virus: state of the question, proportionality principle and informed consent - Pinto Bustamante, Boris Julián (Acta Bioethica, 2016)
Within the current discussions on immunization practices, Human Papillomavirus (HPV) made various challenges from bioethics: firstly, there are controversies regarding the efficacy and safety profile of marketed vaccines, and with respect to their cost-effectiveness. Around the discussion is evident in empirical studies that the informed consent process does not provide the necessary elements for the patients and their legal representatives can participate meaningfully in the process of making decisions about vaccination. This article presents an overview of the status of the issue, with an analysis from bioethics from the principle of proportionality and the deliberative syncretic method and suggests some input to optimize the process of informed consent for the HPV vaccine.